Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/jtd-22-534
|View full text |Cite
|
Sign up to set email alerts
|

Moricizine prevents atrial fibrillation by late sodium current inhibition in atrial myocytes

Abstract: Background: Enhanced late sodium current (INaL) is reportedly related to an increased risk of atrial fibrillation (AF). Moricizine, as a widely used anti-arrhythmia drug for suppressing ventricular tachycardia, has also been shown to prevent paroxysmal AF. However, the mechanism of its therapeutic effect remains poorly understood.Methods: Angiotensin II (Ang II) was induced in C57Bl/6 mice (male wild-type) for 4 weeks to increase the susceptibility of AF, and acetylcholine-calcium chloride was used to induce A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In recent years, the incidence of atrial fibrillation (AF) has been growing with the aging of the population. The treatment of AF mainly includes antiarrhythmic drugs and surgery ( 1 ). Catheter ablation, as a new technology of surgery, has become one of the main methods to treat AF due to its advantages of less trauma, low recurrence rate, and high success rate ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the incidence of atrial fibrillation (AF) has been growing with the aging of the population. The treatment of AF mainly includes antiarrhythmic drugs and surgery ( 1 ). Catheter ablation, as a new technology of surgery, has become one of the main methods to treat AF due to its advantages of less trauma, low recurrence rate, and high success rate ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high extracellular Ca 2+ levels may increase the release of norepinephrine from sympathetic end terminals ( 48 , 49 ). This together results in a decrease in the atrial effective refractory period creating an atrial substrate for AF and in an increase of the incidence of inducible AF and its duration, reflecting the pathological process of AF ( 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different roles of the left (LA) and right (RA) atria in the initiation and maintenance of AF have been widely debated. Previous studies showed that LA is typically the location of high-frequency sources in both paroxysmal and chronic AF resulting in LA-to-RA frequency differences during AF, which are associated with inter-atrial differences in structure and K + and Na + channel proteins (4)(5)(6)(7)(8). LA fibrosis may have a greater impact on AF initiation and maintenance than RA fibrosis, which also may contribute to LAto-RA frequency differences during AF (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The latter drugs can accelerate the second and third phases of repolarization, thereby shortening the action potential duration and prolonging the effective refractory period. A study of moracizine treatment for atrial arrhythmias found that it significantly reduced the incidence of AF and of AF burden without affecting the sinus rhythm [5]. Metoprolol is a selective β1 receptor blocker that can reduce the heart rate and cardiac output (CO) at rest and during exercise, reduce blood pressure, and slow atrioventricular conduction to decrease the sinus rhythm [6].…”
Section: Introductionmentioning
confidence: 99%